Temporal Eating Patterns and Weight Status Among US Adults in the American Time Use Survey (ATUS). (29th May 2020) - O'Connor, Sydney; Reedy, Jill; Graubard, Barry; Kant, Ashima; Czajkowski, Susan; Berrigan, David
Abstract: Objectives: In addition to diet quality and quantity, the timing of eating in relation to the circadian rhythm may impact weight status and overall health. Experimental studies suggest that a shorter eating window and extended overnight fast may promote metabolic health and weight loss. Additionally, eating early in alignment with the circadian peak in metabolism may be protective, while eating close to the biological night may promote weight gain. This study examined cross-sectional associations of temporal eating patterns with weight status. Methods: This study used the Eating & Health Module of the 2006–08 and 2014–16 American Time Use Survey (ATUS), a nationally-representative sample of US adults with a 24hr time use diary (4am – 4am). Respondents ages 18–64 years with a body mass index (BMI) 18.5–50.0 kg/m 2 were included. Sleep and primary/secondary eating activities were used to define three temporal eating patterns: duration between (a) end of sleep and first eating activity (morning fast); (b) first and last eating activity (eating window); and (c) last eating activity and beginning of sleep (evening fast). Multinomial logistic regression models, accounting for ATUS survey design, were used to examine associations between each temporal eating pattern and BMI (normal weight, overweight, obese), controlling for age, sex, education, employment, household size, race/ethnicity, total sleep time, weekend, season, and year. Results: A total of 38, 717 respondents were included. For each hour increase in morning fast, the odds of being normal weight (vs. obese) was 0.95 (95% CI: 0.94–0.97). For each one hour increase in eating window, the odds of normal weight (vs. obese) was 1.05 (95% CI: 1.04 – 1.06), and for each hour increase in evening fast, the odds of normal weight (vs. obese) was 0.96 (95% CI: 0.95 – 0.98) (all P < 0.0001). Similar trends were seen for overweight (vs. obese) (all P < 0.05). Conclusions: Though findings for morning fast are consistent with hypotheses, findings for eating window and evening fast are not. Limitations include a single observation day, which may not reflect usual eating patterns and does not consider dynamic weight trajectories, potential influence of bias and misclassification error, and lack of information on diet quality and quantity, which should be considered in future studies. Funding Sources: N/A